2013
DOI: 10.1179/2045772313y.0000000126
|View full text |Cite
|
Sign up to set email alerts
|

Vertical ground reaction force-based analysis of powered exoskeleton-assisted walking in persons with motor-complete paraplegia

Abstract: Objective: To use vertical ground reaction force (vGRF) to show the magnitude and pattern of mechanical loading in persons with spinal cord injury (SCI) during powered exoskeleton-assisted walking.Research design: A cross-sectional study was performed to analyze vGRF during powered exoskeletonassisted walking (ReWalk™: Argo Medical Technologies, Inc, Marlborough, MA, USA) compared with vGRF of able-bodied gait. Setting: Veterans Affairs Medical Center. Participants: Six persons with thoracic motor-complete SCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 14 publications
1
94
3
1
Order By: Relevance
“…The increased VO 2 for walking, above that of sitting and standing, is evidence that additional effort from the user is required to perform ambulation in the exoskeleton (i.e., the exoskeleton is not performing all of the work for ambulation). Previous investigations measuring pressure under the foot when ambulating in the exoskeleton demonstrated that the less skilled participants were not loaded to the same degree as those who were more proficient [29]. Although measurements of pressures on the crutches were not observed, it was hypothesized that the less skilled participants offloaded some weight onto their crutches.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The increased VO 2 for walking, above that of sitting and standing, is evidence that additional effort from the user is required to perform ambulation in the exoskeleton (i.e., the exoskeleton is not performing all of the work for ambulation). Previous investigations measuring pressure under the foot when ambulating in the exoskeleton demonstrated that the less skilled participants were not loaded to the same degree as those who were more proficient [29]. Although measurements of pressures on the crutches were not observed, it was hypothesized that the less skilled participants offloaded some weight onto their crutches.…”
Section: Discussionmentioning
confidence: 97%
“…Once the right leg has completed the swing motion, the user shifts his or her body weight onto this leg, which will lead to the unweighting of the left leg and triggering the left leg to pass through the swing portion of the gait. The subsequent steps are initiated by the uninterrupted shifting onto the contralateral leg that has just completed the swing phase, resulting in continuous ambulation, similar to natural walking [29]. The device can be triggered to stop walking and return to the standing mode if no forward tilt is sensed for at least 2 s. The other method for stopping, which all participants choose to use the majority of the time, was performed by not fully weight shifting laterally so that their body position failed to allow the swing leg to clear the floor, resulting in activation of a safety mechanism that senses sufficient resistance to movement to cause the device to discontinue walking.…”
Section: Powered Lower-limb Exoskeleton Description and Trainingmentioning
confidence: 99%
“…Overall, our findings were positive and suggested that the training programme may be of benefit to further upright mobility exercise with the population because ankle dorsi-flexion and hip extension are inherently required for normal gait. [26] concluded that the gait cycle shown by independent users of the ReWalk TM exoskeleton was similar to that of 'normal' human gait with regard to kinetic biomechanical analysis of phases. Even assisted users demonstrated 'heel strike' 'mid stance' and 'toe off ' phases of the gait cycle which inherently require DF and HE [26].…”
Section: Resultsmentioning
confidence: 91%
“…The participants wore a wireless controller around the wrist and the battery and computer in the backpack weighing 3.5kg [26]. The training programme took place over five days.…”
Section: The Training Programmementioning
confidence: 99%
“…Based on the time of the training program, five studies had a shorter training period [26,45,[52][53][54][55], while several weeks to months were reported in other studies [32,51]. Training protocol was being done on the different surfaces including sidewalk, grass, or stairs [56][57][58]. Yong et al used the training protocol with powered gait orthosis on the treadmill to increase confidence of SCI subjects and improvement of the walking speed on them [59].…”
Section: Orthotic Gait Training Protocolmentioning
confidence: 99%